Target-plane deposition of diamond-like carbon in pulsed laser ablation of graphite - Yap, S.S.; Tou, T.Y. (ELSEVIER SCIENCE BV, 2007)
In pulsed Nd:YAG laser ablation of highly oriented pyrolytic graphite (HOPG) at 10(-6) Torr, diamond-like carbon (DLC) are deposited at laser wavelengths of 1064, 532, and 355 nm on substrates placed in the target-plane. These target-plane samples are found to contain varying sp(3) content and composed of nanostructures of 40-200 nm in size depending on the laser wavelength and laser fluence. The material and origin of sp(3) in the target-plane samples is closely correlated to that in the laser-modified HOPG surface layer, and hardly from the backward deposition of ablated carbon plume. The surface morphology of the target-plane samples shows the columnar growth and with a tendency for agglomeration between nanograins, in particular for long laser wavelength at 1064 nm. It is also proposed that DLC formation mechanism at the laser-ablated HOPG is possibly via the laser-induced subsurface melting and resolidification. (C) 2007 Elsevier B.V. All rights reserved.